(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Edupark is an educational park concept that combines educational and recreational elements in a contextual and enjoyable learning environment. Meer Von Kandi was selected as the location for developing a physics learning module due to its rich potential for physics concepts, strategic location, and the fact that it has not been previously used as a research object. Attractions at this site such as a water slide, tipping bucket, and a replica of a Dutch windmill contain various physics concepts including work and energy, motion kinematics, force, and rotational dynamics. This study uses the EDUPARK development model, which consists of seven stages, focusing on the first three stages, namely EDU: Edupark Finding, Direct Observation, and Understanding of Teacher, Student, and Curriculum Characteristics. Data were collected through direct observation, teacher interviews, and student questionnaires. The results indicate that most students have a dominant visual learning style, yet their recognition of physics concepts in the tourist site remains low. These findings serve as a fundamental basis for designing a contextual physics learning module based on Problem Based Learning (PBL), which is relevant to the surrounding environment and can enhance students’ interest and understanding in learning physics.